When Women Play: The Relationship between Musical Instruments and Gender Style - Koskoff, Ellen (Canadian University Music Review / Revue de musique des universités canadiennes, 1995)
In many societies, musical roles are divided along gender lines: women sing and men play. Men also sing and women sometimes play; yet, unlike men, women who play often do so in contexts of sexual and social marginality. This essay surveys the literature on women's use of musical instruments in a variety of social and cultural contexts and presents some contemporary anthropological theories regarding the interrelationship between social structure and gender stratification. The author concludes that women's use of musical instruments is related to broader issues of social and gender structure, and that changes in the ideology of these structures often reflect changes that affect women as performers.